Sabato`s Spiritual Crisis - the Way from Science to Literature - Čanović, Ana R (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
The paper is entirely dedicated to the period of spiritual crisis in the life of Argentine writer Ernesto Sabato. In the introduction are stated basic biographical details from the life of the writer for the purpose of further elaboratin of specific period of his life. In the paper are also discussed the issues of Sabato’s consideration of art and science, as well as his views on the meaning of human existence and way of humanization of society. In the central part, the research of Sabato’s path from science to literature was conducted on examples of collections of essays “One and the Universe“, th essays “Before the End" and “The Resistance " and three novels: “The Tunnel", “On Heroes and Tombs" and “Abaddon, The Angel of Darkness." It is concluded that Sabato intentionally and without regret dedicated himself to the world of literature taking into account that for life was not sure about the true reason of his choice.
Keywords: communication; loneliness; spiritual crisis; Ernesto Sabato; writer; SCIENCE; PATHS; literature; life; essays